2020
DOI: 10.3892/ijo.2020.5014
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of 17‑β‑hydroxysteroid dehydrogenase type�2 and its prognostic significance in non‑small cell lung cancer

Abstract: Numerous studies have reported that oestrogens may contribute to the development of non-small cell lung cancer (NSCLC). Although different steroidogenic enzymes have been detected in the lung, the precise mechanism leading to an exaggerated accumulation of active oestrogens in NSCLC remains unexplained. 17-β-Hydroxysteroid dehydrogenase type 2 (HSD17B2) is an enzyme involved in oestrogen and androgen inactivation by converting 17-β-oestradiol into oestrone, and testosterone into 4-androstenedione. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
(117 reference statements)
0
6
0
Order By: Relevance
“…The Kaplan–Meier plotter survival tool evaluated the correlation between more than 30 thousand gene expression and survival in 21 tumors, including breast cancer, lung cancer, GC, etc. Some of the survival data were derived from TCGA database and were also widely used in the basic research of cancer 28–31 . In the present study, we identified a novel GC‐related lncRNA LGALS8‐AS1 through TCGA database combined with the Kaplan–Meier plotter survival tool.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The Kaplan–Meier plotter survival tool evaluated the correlation between more than 30 thousand gene expression and survival in 21 tumors, including breast cancer, lung cancer, GC, etc. Some of the survival data were derived from TCGA database and were also widely used in the basic research of cancer 28–31 . In the present study, we identified a novel GC‐related lncRNA LGALS8‐AS1 through TCGA database combined with the Kaplan–Meier plotter survival tool.…”
Section: Discussionmentioning
confidence: 98%
“…Some of the survival data were derived from TCGA database and were also widely used in the basic research of cancer. [28][29][30][31] In the present study, we identified a novel GC-related lncRNA LGALS8-AS1 through TCGA database combined with the Kaplan-Meier plotter survival tool.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the lncRNA-related ceRNA network, NEAT1 can regulate the expression of Hsd17b2, an mRNA related to steroid metabolism, via miR-181a-5p [ 86 ]. Steroid hormones were inactivated by HSD17B2, and their balance was regulated in a variety of tissues by this molecule [ 87 ]. The elevation in HSD17B2 levels may have been due to the supraphysiological dose of steroid hormone used in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The elevation in HSD17B2 levels may have been due to the supraphysiological dose of steroid hormone used in this experiment. In the circRNA-related reRNA network, circRNA Snx5 regulates Aldh1a2 (a retinoic acid synthase) via miR-129-5p, and elevated Aldh1a2 promotes retinoic acid synthesis, while retinoic acid (a vitamin A metabolite) also exhibits anti-inflammatory effects by preventing oxidative stress [ 87 ]; these findings suggest feedback regulation by mouse prostate tissue in response to intense oxidative stress. The above findings also suggest that steroid hormone-induced BPH in mice was regulated by a dynamic balance of oxidative stress and antioxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…17β-HSD1 catalyzes the conversion of the weakly active E1 to the potent E2, and 17β-HSD2 is its biological counterpart. The expression levels of these enzymes were found to be altered in NSCLC cells compared to healthy tissue, providing a significant prognostic factor and contributing to tumor progression in a stimulatory fashion, probably by increasing the E2/E1 ratio. Selective inhibition of 17β-HSD1 seems therefore a potential approach for the treatment of NSCLC and might be superior to aromatase inhibition in terms of potential side effects: 17β-HSD1 inhibition would result in only a local, intracellular drop in estradiol levels in the target cells while aromatase inhibition would decrease systemic circulating estradiol levels.…”
mentioning
confidence: 99%